Evaporites and the salinity of the ocean during the Phanerozoic: Implications for climate, ocean circulation and life - Hay, William W.; Migdisov, A.; Balukhovsky, A. N.; Wold, C. N.; Flögel, Sascha; Söding, Emanuel (Palaeogeography, Palaeoclimatology, Palaeoecology, 2006)
A compilation of data on volumes and masses of evaporite deposits is used as the basis for reconstruction of the salinity of the ocean in the past. Chloride is tracked as the only ion essentially restricted to the ocean, and past salinities are calculated from reconstructed chlorine content of the ocean. Models for ocean salinity through the Phanerozoic are developed using maximal and minimal estimates of the volumes of existing evaporite deposits, and using constant and declining volumes of ocean water through the Phanerozoic. We conclude that there have been significant changes in the mean salinity of the ocean accompanying a general decline throughout the Phanerozoic. The greatest changes are related to major extractions of salt into the young ocean basins which developed during the Mesozoic as Pangaea broke apart. Unfortunately, the sizes of these salt deposits are also the least well known. The last major extractions of salt from the ocean occurred during the Miocene, shortly after the large scale extraction of water from the ocean to form the ice cap of Antarctica. However, these two modifications of the masses of H2O and salt in the ocean followed in sequence and did not cancel each other out. Accordingly, salinities during the Early Miocene were between 37‰ and 39‰. The Mesozoic was a time of generally declining salinity associated with the deep sea salt extractions of the North Atlantic and Gulf of Mexico (Middle to Late Jurassic) and South Atlantic (Early Cretaceous). The earliest of the major extractions of the Phanerozoic occurred during the Permian. There were few large extractions of salt during the earlier Palaeozoic. The models suggest that this was a time of relatively stable but slowly increasing salinities ranging through the upper 40‰'s into the lower 50‰'s. Higher salinities for the world ocean have profound consequences for the thermohaline circulation of the ocean in the past. In the modern ocean, with an average salinity of about 34.7‰, the density of water is only very slightly affected ...